A influência do processo de construção da Usina Hidrelétrica Baixo Iguaçu na reconfiguração territorial dos municípios atingidos nas regiões Oeste e Sudoeste do Paraná-Brasil - Mendes, Jhones Donizetti (2018)
The establishment of hydroelectric plants in Brazil is seen as a synonymous with progress and development by many social subjects. Nowadays, we are dependent on it, even though 30% of the energy generated by hydroelectric plants is to feed industrial production. Many environmentalists are opposed to the implementation of hydroelectric plants because of their innumerable environmental impacts. Furthermore, in a less notorious way, there are social impacts caused by the implementation of these hydroelectric projects that cannot go unnoticed, due to the complexities of the multi-territorial reconfigurations entailed by such an endeavor. Based on this thought, the present work addresses the influence of the construction process of the Baixo Iguaçu Hydroelectric Power Plant in the territorial reconfiguration of the municipalities affected in the western and southwestern regions of Paraná state, Brazil, including the processes of territorialization, deterritorialization and reterritorialization of the population affected by the construction of the Baixo Iguaçu Hydroelectric Plant (expected to operate in the second semester of 2018), in the municipalities of Capanema, Capitão Leonidas Marques, Planalto, Realeza and Nova Prata of Iguaçu. It is intended as specific objectives to understand the relations of: a) deterritorialization; b) the proposals for reterritorialization and; c) the negotiations between the representatives by the hydroelectric projects and the affected agents. To carry out the research, specific readings were studied to understand the conception of this social category: the affected subject. Several types of media were also consulted about their approach on the subject. Semi-structured interviews were also recorded in audio with various social subjects involved in the case. Through this research, it was possible to understand the reconfiguration of multiterritorialities by the processes of deterritorialization and reterritorialization of the population affected, as well as the negotiations of the territories and the conflicts generated. The claims of the victims occurred under the strong alliance and organization of the population affected, with camps and even confrontation with the police to not let their rights continue being violated, after all, it was not the affected ones that asked the plant to be settled in their region, but it was the plant which came to occupy the space and still does not want to recompense the victims according to what is rightfully theirs. The practice of interviewing the affected subjects allowed an acquaintance of the details of their attachment to the place and the tensions generated before the negotiations. The memory of the victims brings the memories of their experience in this space that can later be a construction site, be underwater, or be within a Permanent Protection Area.